2011
DOI: 10.1089/neu.2010.1682
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ras-GTPase Farnesylation and the Ubiquitin-Proteasome System or Treatment with Angiotensin-(1–7) Attenuates Spinal Cord Injury-Induced Cardiac Dysfunction

Abstract: Cardiovascular diseases are one of the principal causes of death and disability in people with spinal cord injury (SCI). The present study was designed to investigate if acute treatment with FPTIII (an inhibitor of Ras-GTPase farnesylation) or MG132 (an inhibitor of ubiquitin-proteasome pathway [UPS]) or administration of angiotensin-(1-7), also known as Ang-(1-7), (a known inhibitor of cardiac NF-kB) would be cardioprotective. The weight drop technique produced a consistent contusive injury of the spinal cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Varying degrees of myocardial injury and necrosis have been reported following SCI and these mechanisms are generally controversial and poorly characterized (5). Since cardiovascular failure and dysfunction remain leading causes of mortality and disability in patients with SCI, numerous potentially cardioprotective compounds have been recently investigated in animal models, including FPTIII, MG132 or Ang-(1-7) (14). Unfortunately, the majority of successful treatments require immediate administration, generally directly following the initial SCI assault or within the first 6 h. Preliminary studies in the last two decades have indicated that post-SCI administration of PCr, however, is able to effectively improve functional heart contractile recovery, lower diastolic pressure and mediate abnormal myocardial enzyme release relatively late in the acute SCI period (15).…”
Section: Discussionmentioning
confidence: 99%
“…Varying degrees of myocardial injury and necrosis have been reported following SCI and these mechanisms are generally controversial and poorly characterized (5). Since cardiovascular failure and dysfunction remain leading causes of mortality and disability in patients with SCI, numerous potentially cardioprotective compounds have been recently investigated in animal models, including FPTIII, MG132 or Ang-(1-7) (14). Unfortunately, the majority of successful treatments require immediate administration, generally directly following the initial SCI assault or within the first 6 h. Preliminary studies in the last two decades have indicated that post-SCI administration of PCr, however, is able to effectively improve functional heart contractile recovery, lower diastolic pressure and mediate abnormal myocardial enzyme release relatively late in the acute SCI period (15).…”
Section: Discussionmentioning
confidence: 99%
“…Rats were deeply anesthetized with pentobarbital sodium (50 mg/kg) and perfused transcardially as previously described [17], Briefly, the chest of rats was opened and aortic cannulation was carried out using normal saline via the left ventricle of the rat until liquid became clear. Following this, 4% paraformaldehyde in PBS (300 ml) was used for continuous perfusion, and the perfusion was stopped when the liver was white and the limbs and trunk were stiff.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…The recently discovered non-canonical axis of the RAS including angiotensin-(1-7) which acts via the G protein-coupled receptor (GPCR) Mas exert mostly opposite functions to the classical RAS (Bader et al, 2018) and the Ang-(1-7)-Mas axis has been shown to play a key role in the maintenance of the structure and function of the heart (Santos et al, 2006). For example, an acute treatment with Ang-(1-7) before ischemia/reperfusion injury led to significant recovery of heart function following ischemia in hearts isolated from spinal cord injured rats (Benter et al, 2011). The main actions of Ang-(1-7) in the heart are regulation of genes involved in fibrosis in cardiac fibroblasts via Mas, NOreleasing, antioxidative, NO-increasing, direct anti-hypertrophic effects on cardiomyocytes and regulation of endothelial function (Santos et al, 2006;Rabelo et al, 2008;Bader, 2013).…”
Section: Introductionmentioning
confidence: 99%